2016
DOI: 10.1016/j.chom.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The cGAS-STING Defense Pathway and Its Counteraction by Viruses

Abstract: Summary Upon viral infection, host cells mount a concerted innate immune response involving type I interferon and pro-inflammatory cytokines to enable elimination of the pathogen. Recently cGAS and STING have been identified as intracellular sensors that activate the interferon pathway in response to virus infection and thus mediate host defense against a range of DNA and RNA viruses. Here we review how viruses are sensed by the cGAS-STING signaling pathway as well as how viruses modulate this pathway. Mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
302
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(311 citation statements)
references
References 70 publications
4
302
0
5
Order By: Relevance
“…STING’s function has been extensively studied during viral infections due to its major role on the induction of type I interferons ( IFNs ), as reviewed recently [12]. Furthermore, STING plays a role in the development of autoinflammatory diseases, cancer and other sterile inflammations [13].…”
Section: Stimulator Of Interferon Genes: Linking Sensing To Effectivementioning
confidence: 99%
See 1 more Smart Citation
“…STING’s function has been extensively studied during viral infections due to its major role on the induction of type I interferons ( IFNs ), as reviewed recently [12]. Furthermore, STING plays a role in the development of autoinflammatory diseases, cancer and other sterile inflammations [13].…”
Section: Stimulator Of Interferon Genes: Linking Sensing To Effectivementioning
confidence: 99%
“…Moreover, IFI16 contributes to enhanced cGAMP production by cGAS in human cells macrophages [38]. It is important to mention that cGAS can also be implicated in sensing RNA viruses [12]. In an intriguing study, Vermeire et al reported that activated CD4 + T cells sense HIV-1 infection through cGAS, originally described as a DNA sensor, and promote a type I IFN response, although it remains unknown how [49].…”
Section: Dissecting Sting Signalingmentioning
confidence: 99%
“…To search for new DNA sensors, several groups identified STING (also known as MITA, MPYS, ERIS and TMEM173) as a key player in the process of cytoplasmic DNA sensing (Ishikawa and Barber, 2008; Jin et al, 2008; Sun et al, 2009; Zhong et al, 2008). STING is essential for innate immune responses against DNA viruses, bacteria, retroviruses, certain RNA viruses and protozoan parasites (Ma and Damania, 2016; Paludan and Bowie, 2013). STING deficient cells fail to produce type I interferons post cytoplasmic DNA stimulation (Ishikawa and Barber, 2008) and STING knockout mice are extremely susceptible to herpes simplex virus 1 infection (Ishikawa et al, 2009).…”
Section: Innate Immune Responses Induced By Dna Sensorsmentioning
confidence: 99%
“…As one family of the most successful pathogens, herpesviruses have evolved numerous intricate strategies to manipulate, evade and exploit host immune response (Ma and Damania, 2016). Coevolving with their hosts, herpesviruses are expected to leave footprint on host immune system via an arms race between host immune defense and viral evasion thereof.…”
Section: Introductionmentioning
confidence: 99%